Kant and Husserl and the problem of an a priori ontologization and deformalization - Łaciak, Piotr (Folia Philosophica, 2007)
The article presents two conceptions of a priori cognition, i.e. that of Kant and Husserl. Kant’s and Husserl’s positions differ as to the basis of importance of a priori. Kant conducts subjectivisation of a priori because, in his opinion, a priori criteria, such as generalization and necessity, have their basis in the recognising object, and, at the same time, express a subjective inability to present them in other way. Husserl, on the other hand, ontologises a priori, saying that aprioriness is grounded in the essence, and, as such, expresses an objective deriving from the essence’s inability to be in a different way. However, a consequence of a phenomenological ontologization of a priori is a discovery of a material a priori. The aritcle shows that it is possible to see an analogy between Kant’s and Husserl’s standpoints in terms of the scope of aprioriness. Kant’s subjectivisation of a priori, though, does not imply a total formalization of what is a priori because Kant is a creator of an idea of an un-clear synthetic a priori, where one can find similarities to Husserl’s material a priori.